2015
DOI: 10.1097/igc.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms of Toll-Like Receptor 9 −1486T/C and 2848G/A in Cervical Cancer Risk

Abstract: This meta-analysis indicates that TLR9 (-1486T/C, rs187084)-but not TLR9 (2848G/A, rs352140)-may be a risk factor for cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…A previous meta-analysis on the relationship between TLR9 polymorphisms rs352140 and rs187084 and cervical cancer risk conducted by Mu et al is consistent with our results [ 37 ]. There were five studies of rs352140 and four case-control studies of rs187084 in the study of Mu et al that assessed the correlation between TLR9 SNPs and cervical cancer risk.…”
Section: Discussionsupporting
confidence: 93%
“…A previous meta-analysis on the relationship between TLR9 polymorphisms rs352140 and rs187084 and cervical cancer risk conducted by Mu et al is consistent with our results [ 37 ]. There were five studies of rs352140 and four case-control studies of rs187084 in the study of Mu et al that assessed the correlation between TLR9 SNPs and cervical cancer risk.…”
Section: Discussionsupporting
confidence: 93%
“…These variants may exert various influences on the expression or function of a particular gene. 14 , 15 Even with the potential importance of HOTAIR in carcinogenesis, only a few studies have investigated the effects of HOTAIR SNPs on cancer susceptibility. For example, Guo et al reported that the mutated T allele of rs12826786 in HOTAIR could increase the risk of developing gastric cancer and was associated with TNM stage.…”
Section: Introductionmentioning
confidence: 99%
“…Another study analyzed the influence of three TLR9 polymorphisms on multiple cancers, and in the case of the TLR9-1237 TC (rs5743836) SNP, found a protective effect of the C variant allele on digestive system tumors and breast cancer. In contrast to the SNP TLR9-1486 CT (rs187084), there was a high risk for C wild allele carriers in cancer development, particularly in the case of cervical cancer in both the Chinese[13,24] and Caucasian populations[25]. Tian et al[13] stratified the population by race to eliminate heterogeneity, and demonstrated for the rs187084 SNP that the influence of heterogeneity decreased when stratified only among the Chinese population.…”
Section: Discussionmentioning
confidence: 99%